The Impact of School Level and Gender on the Future Existence of the Teaching Profession - Islami, Nelita Indah; Sunarya, Yaya; Najib, Fina Ainun (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
This study is a descriptive quantitative research that aims to determine the effect of school level and gender on the existence of the teaching profession as a future job. The sample of this study consisted of senior high school students from senior high school, vocational high school, and senior high school, with a total of 90 people. Data were collected from distributing questionnaires and analyzed using multiple linear regression analysis with the IBM Statistic 24 application: 1) School level has no positive and significant effect on the existence of the teaching profession as a future profession, 2) Gender has a positive and significant effect on the existence of the teaching profession as a future profession, and 3) School level and gender have a negative and significant effect on the existence of the teaching profession as a future profession. Keywords: school level, gender, the existence of the teaching profession.